The research and analysis of the chocolate nut butter with polyfunctional properties - Кондратюк, Наталія Вячеславівна; Гаркуша, Ігор Миколайович (Eastern-European Journal of Enterprise Technologies, 2016)
The usefulness of the protein and fat composition consisting of whey and blended mixture of vegetable oils in the production technology of chocolate nut butter with a sweet extract from stevia leaves is theoretically proved and verified under production conditions. The composition of the fatty base of the product comprising a mixture of refined sunflower oil and palm oil is developed. The paper examines the polyfunctionality of the chocolate nut butter on the human body, which is due to a high content of whey protein, polyunsaturated fatty acids of vegetable oils and complete replacement of sugar with the sweet extract from stevia leaves. The study of organoleptic characteristics and the chromatographic quantitative assessment of fatty acid and amino acid composition of the final product revealed that the resulting composition has a high nutritional and biological value. Adding the blended fat composition favorably affects the structure and fatty acid composition of the butter, allowing to obtain a product of a given structure and properties.